HYDRAULIC RESISTANCE OF SUBMERGED FLEXIBLE VEGETATION - Stephan U.; Gutknecht D. (My University, 2002)
The main research objective consisted in analysing the influence of roughness caused by aquatic vegetation (av), in particular submerged macrophytes, on the overall flow field. These plants are highly flexible and behave differently depending on the flow situation. They also react substantially to the flow field and thus, the roughness becomes variable and dynamic. Conventional flow formulas, such as the Manning or the Strickler formula, are one-dimensional and based on integral flow parameters. They are not suitable for quantifying the roughness of av, because the flow is complex and more dimensional due to the variable behaviour of the plants. Therefore, the present investigation concentrates on the definition of a characteristic hydraulic roughness parameter to quantify the resistance of av. Within this investigation laboratory experiments were carried out with three different types of av, chosen with respect to varying plant structures as well as stem lengths. Velocity measurements above these plants were conducted to determine the relationship between the hydraulic roughness and the deflected plant height. The deflected plant height is used as the geometric roughness parameter, whereas the equivalent sand roughness based on the universal logarithmic law modified by Nikuradse was used as hydraulic roughness parameter. The influence of relative submergence on the hydraulic roughness was also analysed. The analysis of the velocity measurements illustrates that equivalent sand roughness and zero plane displacement of the logarithmic law are correlated to the deflected plant height and are equally to this height.
Keywords: OPEN-CHANNEL FLOW; FLEXIBLE VEGETATION; ROUGHNESS; SUBMERGED FLOW